ANALISIS KUALIFIKASI YANG DIBUTUHKAN LULUSAN AKUNTANSI UNTUK MEMASUKI INDUSTRI PERBANKAN DI INDONESIA - Prastomo, Nikku Dwiky; Prabowo, Tri Jatmiko Wahyu; Muid, Dul (JAB (Jurnal Akuntansi & Bisnis), 2016)
This study aims to analyze skills that are required by accounting graduates to work in the banking industry in Indonesia. Furthermore, it is to determine the extent of Kualifikasi Nasional Indonesia (KKNI) accounting majors were able to answer the needs of the banking industry as an employer. Banking as a service sector industry is positioned as a market by the University has specific needs in the process of absorption of the freshgraduates. Qualifications can be determined by the needs of the dimensions of generic skills that are demanded by employers, as well as the expectations of the banking industry to accounting graduates can be known through the perception of the banking industry as a market. This study used qualitative methods in the form of questionnaires and interviews with managers and teaching staffs under the auspices of the personnel department which is owned by the state-owned banking industry (BUMN). The method of determining the target used was purposive sampling with certain positions as the criteria. The number of target obtained for the questionnaire and the interview are 50 respondents and 11 interviewees. There are additional resources added from Accounting Diponegoro University graduate who worked in the banking industry. The research questions is answered by comparing answers to the questionnaire with the results of the interview. The results showed that in to work in banking industry the graduates should not only have the hardskill: master the basic accounting, banking industry is also very demanding graduates to have soft skills include: teamwork, positive work attitude / motivation in working, analytical abilities and problem solving, a strong work ethic, communication skills, flexibility and adaptability in work. It draws on previous research which industries require these dimensions. Another thing that is expressed by many speakers is the softskill of accounting graduates still can not reach the expectations of the banking industry in terms of communication skills in the work. An interesting finding obtained from the interview is about the financial engineering. Other obtained results were also in terms of improving the accounting curriculum at universities which is according to iinterviewees' perceptions the university is less soft skill training for students, as well as the accounting curriculum that is still not following the trend of emerging industries. Keywords: generic skill, accounting graduates, Kerangka Kualifikasi Nasional Indonesia (KKNI), accounting education